Gerakan Remaja Kreatif dalam Mengelola Sampah Di Desa Banaran Kecamatan ‎Tembarak Kabupaten Temanggung - Fika Khalwa Ngaisah; Ikhsan Salafudin (Jurnal Pengabdian Agro and Marine Industry, 2021)
Abstract            The creative youth movement of Banaran Tembarak Temanggung Village is an activity that can be said to be normal, but in carrying it out it is not as easy as turning the palm of the hand because of problems arising from people's unconsciousness that they will process waste according to its type, as for several programs that have been realized with The good things in the village of Banaran Tembarak Temanggung are: (1) the stages of planning with social analysis, namely "with activities that begin with conducting interviews. (2) the stage of exploring the potential in the form of strengths, weaknesses, opportunities and also challenges that exist in the village youth community Banaran Tembarak Temanggung which then raises the results of a new social group to manage waste. (3) the evaluation stage is the last stage by conducting a re-assessment and product sales plan with the youth movement of Banaran Tembarak Temanggung village in the management of plastic waste recycling. Meanwhile, in terms of strengths, the team found many ideas and ideas in making other items or works.Keywords : rubbish, teenager and processingAbstrak            Gerakan remaja kreatif Desa Banaran Tembarak Temanggung merupakan kegiatan yang bisa di katakan sudah biasa akan tetapi dalam menjalankannya tidaklah semudh membalikkan telapak tangan karena adanya masalah yang timbul dari ketidak sadaran masyarakat akan mengolah sampah sesuai dengan jenisnya, adapun beberapa program yang telah terealisasi dengan baik di desa Banaran Tembarak Temanggung adalah: (1) tahapan rencana dengan analisis sosial yaitu dengan kegiatan yang diawali dengan melakukan wawancara . (2) tahapan mendalami potensi berupa kekuatan, kelemahan, peluang dan juga tantangan yang ada dalam komunitas remaja desa Banaran Tembarak Temanggung yang kemudian memunculkan hasil kelompok sosial baru untuk mengelola sampah. (3) tahapan evaluasi yaitu tahapan terakhir dengan melakukan pengkajian ulang dan rencana penjualan produk bersama Gerakan remaja desa Banaran Tembarak Temanggung dalam pengelolaan daur ulang limbah plastik. Sedangkan dalam hal kelebihan, tim menemukan banyak ide dan gagasan dalam membuat barang atau karya-karya yang lain.Kata kunci : Sampah, remaja dan pengolahan